Life style portrait (Psychographics) of the Turkish female consumers and of different social classes - Sever, Leyla (My University, 1991)
unknown
Keywords: Genel yönetim; Pazar araştırması ve analizi; Pazarlama yönetimi; TÜKETİCİ ARAŞTIRMALARI-TÜRKİYE; TÜKETİCİ DAVRANIŞI-TÜRKİYE